Differences in Experienced Memory Qualities between Factual and Fictional Events - Gander, Pierre (Journal of cognition and culture, 2023)
The experienced qualities of memories of factual and fictional events have been little researched previously. The few studies that exist find no or few differences. However, one reason to expect differences in memory qualities is that processing of fact and fiction seem to involve activation of different brain areas. The present study expands earlier research by including a wider range of memory qualities, using positive and negative events, and three time-points: immediately after, after a ten-minute delay and after a five-week delay. Participants (N = 52) read four short stories in English, labelled either fact or fiction, and rated memory qualities on 7-point scales. Results show no differences; however, an interaction was found between fictionality and story emotional valence, in that memories of negative fictional stories are rated as more clear. The higher clarity can be explained by previous findings that negative events from stories are in general remembered in more detail, in combination with the idea that fiction entails simulation to a higher degree than fact. The conclusion is that although a difference in memory qualities between fact and fiction was found in one case, memory qualities seem not to play an operative role when the memory system distinguishes fact from fiction.